Theory and Observation: A Perspective on Consumer Trip Behaviour and the Decline of the Ontario Hamlet - Norris, Darrell (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
One reason that classical central place theory has relevance to past patterns and places is that it assumes that consumers make single purpose shopping trips with invariant frequency. An alternative theoretical model incorporating multi-purpose trips is offered, which yields an expected structure of markets and places. Findings are corroborated by the post-office markets of the eastern part of Grey County, Ontario, in the late-nineteenth century. The results suggest that the decline of small places in Ontario was well-established before the advent of the automobile.